Climate change and the resurgence of waterborne diseases: Focus on Sub-Saharan Africa - Sandy Moore; Rita Colwell (Field Actions Science Reports)
Climate change, driven primarily by human activities, leads to persistent shifts in global temperatures and weather patterns. These changes trigger more frequent and intense weather events, which impact populations through both direct and indirect consequences. In particular, populations in Sub-Saharan Africa face heightened risks from climate change due in part to inadequate infrastructure and limited climate resilience. Climate change has significant implications for waterborne diseases, such as cholera, typhoid fever, schistosomiasis and hepatitis A, which affect populations throughout Sub-Saharan Africa. Limited access to clean water, sanitation, and hygiene infrastructure constitute significant risk factors for such diseases. Extreme climate-related events exacerbate these risks. For example, flooding can lead to contaminated water sources, while droughts compromise water quantity and quality. Additionally, extreme weather events can cause malnutrition, population displacement and disrupt livelihoods, further increasing vulnerability to diseases. Mitigating climate change involves reducing greenhouse gas emissions and transitioning to cleaner energy sources. However, short- to medium-term prevention and preparedness can minimize the impacts of waterborne diseases. To prevent waterborne diseases in Sub-Saharan Africa, it is crucial to improve access to safe drinking water, sanitation and hygiene infrastructure.